Basic College Mathematics (10th Edition)

Published by Pearson
ISBN 10: 0134467795
ISBN 13: 978-0-13446-779-5

Chapter 9 - Basic Algebra - 9.6 Solving Equations - 9.6 Exercises - Page 671: 65



Work Step by Step

We are given the equation $-\frac{3}{4}m=-3$. Multiply both sides by $-\frac{4}{3}$. $(-\frac{3}{4}m\times-\frac{4}{3})=m=-3\times-\frac{4}{3}=\frac{3\times4}{3}=\frac{12}{3}=4$ Therefore, $m=4$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.